The Problem Of Preserving National-Spiritual Values In The Context Of Globalization - Alisher Olimjonovich Xakimov (Euro Asian Journal Publishing, 2024)
it seems that spirituality is a criterion that leads a person to spiritual purity, and strengthens and exalts his soul with the rays of faith – faith. The place of a person in society is determined not by his material assets, but by his high spiritual image. Spirituality serves as a bridge connecting ancestors to generations, the past to today, and the present to the future
Keywords: value; spirituality; culture; human